Recurrence patterns of retroperitoneal leiomyosarcoma and impact of salvage surgery. Issue 3 (29th May 2017) - Ikoma, Naruhiko; Torres, Keila E.; Lin, Heather Y.; Ravi, Vinod; Roland, Christina L.; Mann, Gary N.; Hunt, Kelly K.; Cormier, Janice N.; Feig, Barry W.
Abstract : Background: Optimal treatment strategies for retroperitoneal leiomyosarcoma (RPLMS), particularly recurrent disease, are unknown. Methods: We searched the tumor registry at The University of Texas MD Anderson Cancer Center (MDACC) to identify patients with RPLMS treated between 1994 and 2013. Results: We identified 172 patients with a diagnosis of a RPLMS. Among the 85 patients who underwent complete resection included in the survival analysis, the median overall survival (OS) was 8.3 years (95% confidence interval [CI], 5.7‐12.3), 5‐year local recurrence rate was 21%, and 5‐year distant metastasis rate was 47%. Among 114 patients who experienced recurrence, patients who underwent salvage surgery for recurrent disease had longer OS after recurrence than patients who did not undergo salvage surgery (median survival after recurrence 5.6 vs 3.3 years, 3‐year OS rates after recurrence 72.6% vs 58.1%, HR 0.402 [95%CI, 0.243‐0.666]; P  = 0.0004). Whether salvage surgery was performed for local or distant recurrence was not associated with OS. Patients who had a longer disease‐free interval (≥12 months) had better progression‐free survival after salvage surgery than those who had a shorter interval (HR, 0.437 [95%CI, 0.244‐0.783]; P  = 0.0055). Conclusions: We recommend that salvage surgery be considered for selected patients with local or distant recurrence of RP LMS.